'The Only Thing "Womanish" is the Composer': Music at Nineteenth-Century Exhibitions of Women's Work. Issue 3 (23rd October 2019) - Kirby, Sarah
Abstract: The 1880s saw a burgeoning of exhibitions of 'Women's Work' across the world. These events focused on the artistic and industrial abilities of women, signifying an unprecedented shift away from the emphasis usually placed on maleness and masculinized technology in contemporary exhibition culture. The first Exhibition, held in Bristol in 1885, included a musical novelty: a concert entirely of works composed by women. The next, in Sydney in 1888, included a whole series of such concerts. These concerts—containing works by Kate Loder, Clara Wieck, Fanny Hensel, Agnes Zimmermann, and Maude Valérie White—were extraordinarily well received, applauded in both concept and execution. Yet, their reception appears paradoxical against the contemporary critical climate. In both Britain and Australia, the 'question' of women composers was widely debated, and works met with condescension or hostility. By exploring the expectations surrounding displays of 'women's work', I argue that it was the exhibition context itself that influenced the reception of this music. While Exhibitions were conventionally seen as male-gendered events, 'Women's' Exhibitions allowed organizers to blur the distinctions between private and public space. Similarly, while women composers were criticized for their encroachment in the male concert sphere, these Exhibitions also blurred these boundaries and gave critics an appropriate 'feminine' framework through which to view and critique the works.